2018
DOI: 10.3389/fphys.2018.00557
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Apelin in Cardiovascular Diseases, Obesity and Cancer

Abstract: Apelin is an endogenous peptide identified as a ligand of the G protein-coupled receptor APJ. Apelin belongs to the family of adipokines, which are bioactive mediators released by adipose tissue. Extensive tissue distribution of apelin and its receptor suggests, that it could be involved in many physiological processes including regulation of blood pressure, body fluid homeostasis, endocrine stress response, cardiac contractility, angiogenesis, and energy metabolism. Additionally, this peptide participates in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
166
1
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(182 citation statements)
references
References 144 publications
3
166
1
12
Order By: Relevance
“…Apelin is an endogenous peptide that belongs to the adipokines family and a ligand for the orphan G protein‐coupled receptor (APJ) . In normal conditions, APJ is expressed in the vascular smooth muscle cells, endothelium, and myocardial cells, and plays an important role in regulating blood pressure, cardiac contractility, and angiogenesis …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apelin is an endogenous peptide that belongs to the adipokines family and a ligand for the orphan G protein‐coupled receptor (APJ) . In normal conditions, APJ is expressed in the vascular smooth muscle cells, endothelium, and myocardial cells, and plays an important role in regulating blood pressure, cardiac contractility, and angiogenesis …”
Section: Introductionmentioning
confidence: 99%
“…Recent findings suggest that the apelin/APJ system may be involved in the pathophysiology of cardiovascular diseases . For the first time, Földes and colleagues reported that apelin may be involved in the pathogenesis of heart failure in the human .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that this apelin-mediated signalling is connected to heart failure and ischemic heart disease. Furthermore, apelin participates in the pathology of diabetes by playing a key role in increasing glucose uptake and insulin sensitivity [60]. Another important dysregulated signalling pathway was atherosclerosis signalling.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β pathway is involved in in ammation and tissue remodeling mediated by endothelial cells, and immune activation, which support the importance of TGF-βpathway in KD occurrence and outcomes [15,16].CD34 positive cells with enhanced adhesive and homing properties facilitates immune cells homing to the in ammatory sites and mediates in ammatory and immune responses [17].CXCL1, as the chemokine ligand, presents on endothelial surface and mediates immune responses by recruitment of neutrophils and monocytes [18,19].APLN(apelin) is a vasoactive peptide and an endogenous ligand for APJ receptors. APLN/APJ receptor system plays a vital role in regulation of vascular function, including vascular tone, angiogenesis, proliferation, and permeability [20,21].In addition, APLN/APJ system also mediates the anti-in ammatory effects of 1,25(OH)2D3 by reduction of pro-in ammatory mediators and adhesion molecules in LPS-stimulated macrophages [22]. PITX2 plays an important role in regulating the differentiation of endothelium and angiogenesis [23,24].Although these studies provide insights into these biomarkers involved in regulation of cardiovascular and immune system, it is yet unknown whether these alterations can be considered as potential indicators for prevention and treatment of coronary artery damage in KD, which needs further investigations.…”
Section: Discussionmentioning
confidence: 99%